Técnicas de microbiolização de sementes de milho, feijão, nabo forrageiro e aveia preta. - Junges, Emanuele (2012)
The objective of this study was the effect of leverage microbiolization seed corn, beans, forage radish and black oat with Trichoderma spp. and Bacillus subtilis by physiological conditioning techniques, suspension of biological structures and film coating. The microbiolization seeds without additional technique was carried out with commercial products Rhizoliptus® and Agrotrich plus ®. Fluid restriction was held in Manitol + PDA medium for Trichoderma spp. or Bacillus subtilis, were distributed on each plate of each seed culture previously disinfected. When was the first seed radicle protrusion in the other were removed and dried in a laboratory environment for 48 h. The film coating was performed with the addition of the polymer Color Seed ® treatment the syrup containing Trichoderma spp. or product Rhizoliptus. The seeds were dried for 48 h in a laboratory environment. We used a treatment associating film coating and fluid restriction in seed microbiolization with the bodies and their association. The performance of the treatments was assessed by a set of tests in laboratory, greenhouse and field. Trichoderma spp. pathogens associated controls, and has good association with the seeds used. Trichoderma spp. and B. subtilis growth promoting the development of seedlings and plants, with variable response depending on the technique used microbiolization. Under conditions of the germination test roll the association of Trichoderma spp. with the seeds becomes pathogenic, however when tests are conducted on a substrate or soil these harms are not played.